DEVELOPING LEARNER AUTONOMY-BASED FOREIGN LANGUAGE PROFICIENCY ENHANCEMENT MODEL FOR VIETNAM’S PUBLIC OFFICIALS, CIVIL SERVANTS AND PUBLIC EMPLOYEES - Ly, Nguyen Ngoc Luu (VNU Journal of Foreign Studies; Vol 34 No 4DO - 10.25073/2525-2445/vnufs.4287, 2018)
Autonomy is a popular research theme among scholars worldwide. This article explains the selection, analysis, evaluation and deployment of learner autonomy model which is suitable for Vietnam’s public officials, civil servants and public employees to acquire and master foreign languages who would benefit from the State-level research project A study to develop foreign language proficiency enhancement models for public officials, civil servants and public employees in the Customs, Foreign Relations, Tourism and Border Guards sectors for public service delivery amidst the international integration trend in the Northwest conducted by ULIS-VNU under the Program “Science and Technology for sustainable development of the Northwest” coded KHCN-TB/13-18. The article also formulates recommendations on ways to improve foreign language proficiency for Vietnam’s public officials, civil servants and public employees, considering that there is a need for innovation in foreign language teaching and learning methods in order to enable learners to use foreign languages at work effectively.